STRUCTURAL CHANGES IN TRANSLATION AND THEIR EFFECTS ON THE MEANING TRANSFER - Susie Chrismalia Garnida (Universitas 17 Agustus 1945 Surabaya, Prodi sastra Inggris, Fakultas Ilmu Budaya, 2021)
This article discusses the effect of structural change in translation of English text into Indonesian. Data are selected from some bilingual (English-Indonesian) literary works. The result of the study shows that structural changes in the translation affect the accuracy of meaning transfer. On the other hand, structural change may be done for ease of reading, while the complete meaning is expected to be derived from the context or co-text of the structural items. The finding gives some insights of the dynamics of translation, and particularly of the effect of strategy choice on the meaning transfer.